Policy Analysis of Recruitment Selection and Employee Motivation Sharia Cooperative Kosgoro 1957 Banjarmasin - Fanlia Adiprimadana Sanjaya (Hut Publication Business and Management, 2021)
This study aims to determine and analyze the effect of recruitment, selection and motivation of employees. The research method used is qualitative analysis with field research and library research and data analysis from observation, interview, and documentation data collection techniques. This study indicates that employee recruitment and selection is still not as good as in human resource management techniques, and employee motivation is still inadequate. Because the employees of this company are still concurrently with the management of the cooperative, which operationally still does not provide adequate services, namely 2 people with details of 1 manager and 1 staff employee, so that the benefit to customer members as many as 155 people is still inadequate, therefore this cooperative need to plan the recruitment and selection of employees needed as many as 3 people, so the total number of employees of the cooperative is 5 people. Currently, the provision of motivation is only in the form of a low honorarium. Therefore, it is necessary to provide incentives so that employees are more enthusiastic and give non-material explanations such as a pleasant work environment in the form of good office facilities, such as workspaces with good air circulation, multi-media computers complete with the internet. In addition, it is necessary to provide other non-material motivations in the future.